Comparison of a novel un-baffled and a conventional shell-and-tube dry-expansion evaporator. (25th February 2017) - Yin, Y.D.; Zhu, D.S.; Sun, J.F.; Li, X.Z.; Zhang, J.N.; Lin, C.D.
Highlights: A novel un-baffled shell-and-tube dry-expansion evaporator (USTDEE) was developed. The USTDEE has better heat transfer performance than the BSTDEE. The USTDEE has advantages of materials-saving and energy-conservation and so on. Abstract: To overcome the disadvantage of the poor heat transfer performance of the conventional baffle shell-and-tube dry-expansion evaporator (BSTDEE), a novel un-baffled shell-and-tube dry-expansion evaporator (USTDEE), for use in air source heat pumps (ASHPs), was developed and investigated. An experimental platform was built to test the performance of the USTDEE-ASHP and BSTDEE-ASHP. Several parameters, including the overall heat transfer coefficient ( U ) of the USTDEE and BSTDEE, cooling capacity ( Q e ), heating capacity ( Q c ), and coefficient of performance (COP) of the ASHP were investigated. The results show that the COP of the USTDEE-ASHP is higher than that of the BSTDEE-ASHP. The refrigerant charge of the former unit is less than that of the latter, whereas the water pressure drop of the former is greater than that of the latter. With increasing evaporating temperature ( T e ), outside tube Reynolds number ( Re o ) and heat flux ( q i ), the heat transfer performance of the USTDEE is enhanced and is better than that of the BSTDEE. With an increase in condensing temperature ( T c ), the heat transfer performance of the USTDEE and BSTDEE decreases, and the former is worse than the latter. This research indicates that the USTDEE has the advantages of higher heat transfer performance; compact volume and less heat transfer area and has broad prospects in air conditioning heat pump applications.